Women on the Job Market – German Philology Female Graduates Conquer the Major Outsourcing Companies - Grzeszczakowska-Pawlikowska, Beata; Stawikowska-Marcinkowska, Agnieszka (Germanistinnen und Germanisten im Beruf – zwischen Ausbildung und Realität, 2020)
The discussion about the focus of German philology on nontraditional philological subjects such as technical languages or communication in the workplace is not new. It started in the 1960s. However, the discussion intensified after 2004, when Poland joined the European Union. Due to the opening of the borders and the resulting economic changes, the demand for workers with a very good knowledge of German on the Polish labor market has increased significantly. Many companies have moved their production to our country. Therefore, they have become a delicious bite for students and graduates of foreign language philologies. Since German philology at the University of Lodz has for many years been a course mainly chosen by women, an idea arose to analyze its role in the Lodz job market. The results of this study clearly show that Lodz companies see a great demand for educated women who speak foreign languages, with a special focus on German.